Avaliação prognóstica da reserva de fluxo fracionada em diferentes estratos nos pacientes com doença arterial coronariana - Pellegrini, Denise Machado de Oliveira (2021)
Background and objective: There is limited data on clinical outcome of deferred coronary lesions according to functional severity. This study aimed to evaluate the 5 year clinical outcomes of patients with non deferred lesions with FFR ≤0.8 and deferred lesions patients with FFR > 0.8. Methods: From 2013 to 2018 FFR was performed in 218 consecutive patients included in a single center registry. Participants were categorized on the basis of FFR in ischemic FFR group (≤0.8, intervention group, n=55), low-normal FFR group (> 0.8 -0.9, deferred, n=91) and high-normal FFR group (> 0.9, deferred n=72). Primary end point was major adverse cardiac events (MACE), a composite of mortality, myocardial infarction, and target lesion revascularization. Additional secondary endpoints were coronary angiography, hospital admission, and stroke. Results: The baseline characteristics were similar among groups. The median age was 63.2, 65,1 and 64,2 years in group intervention, low-normal and high normal respectively. Most were male and diabetes was present in a significant proportion in the groups. By coronary angiography, stenosis severity was 62%, 56,4% and 54,3% in groups ischemic, low-, and high-normal FFR respectively( p> 0.05). The incidence of MACE was 25.5%, 13,2% and 11,1% respectively (p=0,037). In the the chronic coronary patients subgroup the incidence of e MACE were statistical significant different among the groups (p<,006). New angiography occurred more frequently in ischemic group (27.3%) as compared to low-normal (7.7%) and high-normal (14,3%) FFR patients (p=0.05). Similarly, hospitalar admission occurred in 23.6% in ischemic FFR patients as compared to low-normal 6.6% and high-normal 8.6% FFR patients (p=0.05). Acute myocardial infarction occurred in 1.8%, 3.3% and 1.4% in groups ischemic, low-, and high-normal FFR respectively (p= 0.70) and stroke occurred in 1.8%, 0,0% and 1.4% in groups ischemic, low-, and highnormal FFR respectively (p=0.46). The mean follow up period was 3.5 years. Conclusion: The result of our study allows us to conclude that individuals in the ischemic group have worse outcomes when compared to those in the non-ischemic groups. Among the groups with FFR values considered low normal and high normal, there is no significant difference between these two groups, however these patients should not be considered at low risk for long-term cardiovascular events in view of the possible atherosclerotic plaque progression already demonstrated in previous studies. There is a need for long-term prospective studies to better assess cardiovascular outcomes in non-revascularized patients with FFR above 0.8.